2014
DOI: 10.1590/0104-1169.3182.2417
|View full text |Cite
|
Sign up to set email alerts
|

Participation of adolescents in the Family Health Strategy from the theoretical-methodological structure of an enabler to participation

Abstract: Objective to evaluate the participation of adolescents in the Family Health Strategy, from the theoretical-methodological structure of an enabler to participation. Method a quantitative study, conducted from December of 2010 to March of 2011, with 213 professionals in the FHS in the region of Cariri-Ceará-Brazil. Data were collected through a questionnaire and organized in SPSS 18.0. Results the level of normative participation becomes manifest beginning with the adolescent search for health services, motivate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 11 publications
1
16
0
10
Order By: Relevance
“…21 Regarding the concern about nurses' representational content regarding pregnancy in adolescence, a previous study indicates the main reasons that lead to the participation of adolescents in the home visit: when pregnant or puerperal, when they are ill and when professionals wish to identify risk factors. 22 Regarding the practice of family planning involving adolescents, in order to prevent new pregnancies, this practice was also observed in another study as one of the Regarding the availability of condoms reported by the subjects, a similarity is observed with another study carried out in Rio de Janeiro, where the distribution of the condom was distributed in most of the 147 units of sexual and reproductive health services. 23 And another research reports the distribution of contraceptives (including condoms) to adolescents as a practice performed by 86% of nurses in a FHS.…”
Section: [] We Did a Training Course There At The Arc Which Is Thesupporting
confidence: 67%
See 1 more Smart Citation
“…21 Regarding the concern about nurses' representational content regarding pregnancy in adolescence, a previous study indicates the main reasons that lead to the participation of adolescents in the home visit: when pregnant or puerperal, when they are ill and when professionals wish to identify risk factors. 22 Regarding the practice of family planning involving adolescents, in order to prevent new pregnancies, this practice was also observed in another study as one of the Regarding the availability of condoms reported by the subjects, a similarity is observed with another study carried out in Rio de Janeiro, where the distribution of the condom was distributed in most of the 147 units of sexual and reproductive health services. 23 And another research reports the distribution of contraceptives (including condoms) to adolescents as a practice performed by 86% of nurses in a FHS.…”
Section: [] We Did a Training Course There At The Arc Which Is Thesupporting
confidence: 67%
“…In this perspective, a study with nurses reports that the participation of adolescents in health education actions is focused on the schools. 22 In this context, an integrative review study points to the school as an ideal scenario for the development of health activity, due to the fact that the students spend much of their time in this environment. 24 In addition, despite the difficulties, the FHS has entered the schools through the PSE and has helped in the positive modification of students' lives.…”
Section: [] We Did a Training Course There At The Arc Which Is Thementioning
confidence: 99%
“…[4][5] The use of games is an instrument of the educational process in health that favors participation, debates and exchange of experiences, From a critical perspective in relation to traditional education. 6 The use of educational games for adolescents has shown that playful and participatory work fosters arguments, reflections and collective construction of knowledge among them.…”
Section: Introductionmentioning
confidence: 99%
“…A study, which evaluated the participation of adolescents in the FHS, based on the framework of the theoretical-methodological framework of an enabling participation, 25 helps scale the complexity of serving these customers through the FHts. It was found that the participation of adolescents was predominantly focused on the first level of the reference that indicates the normative participation in which the user is only able to take care of themselves.…”
Section: Discussionmentioning
confidence: 99%